علم اور اقسامِ علم ،اسلامی تعلیمات اورفلاسفہ یونان کی نظر میں: Knowledge and its types through the lens of Greek Philosophers & Teachings of Islam - Tahir Jan, Dr. Muhammad; Fatima, Ishrat; Hussain, Malik Akhtar (Al-Amīr Research Journal for Islamic Studies, 2023)
This research paper delves into the intricate concept of knowledge and its various types within the framework of Islamic teachings. Knowledge holds a pivotal position in Islamic tradition, emphasized through numerous verses in the Quran and teachings of the Prophet Muhammad (SAW). This study employs a qualitative approach, drawing upon Islamic scriptures, scholarly interpretations, and contemporary literature to explore the multifaceted nature of knowledge as perceived within Islam. The paper begins by elucidating the Quranic perspective on knowledge, emphasizing its significance as a means of enlightenment and guidance for humanity. It delves into the classification of knowledge in Islamic epistemology, which encompasses both religious (Ilm al-Din) and worldly (Ilm al-Dunya) knowledge. Furthermore, it explores the distinction between various types of knowledge such as empirical, spiritual, experiential, and revealed knowledge. The research aims to elucidate the diverse classifications of knowledge within Islamic discourse, ranging from religious sciences to empirical sciences, and from experiential knowledge to intuitive knowledge. Moreover, this research paper contributes to a nuanced understanding of knowledge and its typology from an Islamic perspective, offering insights that are both enriching for Islamic scholarship and pertinent for broader interdisciplinary dialogues in the pursuit of knowledge and wisdom. In conclusion, this research contributes to a deeper understanding of knowledge and its diverse manifestations within Islamic teachings. It underscores the relevance of Islamic epistemology in contemporary discourse on knowledge, ethics, and societal progress, offering insights for scholars, educators, and policymakers alike. Keywords: Knowledge, Islamic Teachings, Epistemology, Quran, Hadith, Ethics, Revelation, Reason, Reality, Science.